Pengembangan Multimedia berbasis Inkuiri Terbimbing pada mata pelajaran Ilmu Pengetahuan Alam Kelas VII SMP Negeri 2 Kota Pariaman - Elia Mesra; Darmansyah Darmansyah; Nofri Hendri (Journal of Pedagogy and Online Learning, 2022)
This study aims to produce a guided inquiry-based learning multimedia that is valid, practical, and effective so that it is suitable for use by teachers and students in the learning process.This research belongs to the research and development cluster using the 4D model, namely define, design, develop, and disseminate. The define stage consists of curriculum analysis, student analysis, media analysis and analysis of subject objectives. The Design phase is carried out by designing learning media. The development stage is carried out through validity testing by validators and practicality tests, effectiveness by class VII students at SMP N 2 Kota Pariaman and the last is dissemination or dissemination in the form of media that will be distributed to schools at SMP Negeri 2 Kota Pariaman. Based on the research that has been done at SMP N 2 Kota Pariaman, it has been successfully made learning multimedia. The results of the validity test of the material and media aspects show that the resulting media is very valid, namely, with a score of 148 with an average material validity value of 93.54% and a score of 131 with an average media validity of 87.91%. Meanwhile, students' responses to the products developed were very practical with an average of 94.67% and to measure the level of achievement of student learning outcomes before and after using the media showed tcount > ttable so that the effectiveness trial showed an increase in learning process skills. It can be concluded that the multimedia developed in this study is suitable for use in the learning process.